PENGARUH KEASAMAN BAHAN PEMBENTUKAN LEMBARAN TERHADAP SIFAT PAPAN SERAT BERKERAPATAN SEDANG - Ridwan Achmad Pasaribu; Kayano Purba (Jurnal Penelitian Hasil Hutan, 1986)
Manufacturing trials of medium density fiberboard from logging wood wate have been conducted on a laboratory scale at the Forest Products Research and Dewlopment Centre, Bogor. Wood sample used in this study were obtained from South Sumatera logs of having a fairly wide range of specific gravity from 0.37 - 0.61. Pulp preparation were carried out by using the conventional cold caustic soda process at concentration of 36 gram per liter; wood to liquor ratio of 1 to 7 and soaking time of 24 hours. In this experiment the role of the pH of the slurry was investigated at seven levels being from pH 3 to pH 8 with one pH interval. Medium density fiberboard are formed by applying cold pressure of 10 kg/cm2 for 5 minute, and hot pressure of 25 kg/cm2 for 3 minute at 180°C. The pulp yield and alkali consumption were tested, according to the Libby experiment pulping by cold caustic soda process. Average pulp yielda were between 89,6 - 91,2 per cent with relatively high lignin content ranges from 17,2 - 24,8 per cent. The alkali comsumptions in the spent liquor throughout the experiment were between 10, 7 and 13, 7 per cent. This experiment reveals that except for density, other properties were significantly in fluenced by the level of pH. Medium density fiberboard produced from slurry of having the pH of 3, 4, 5, 6 and 7 appear to have the density, water absorption, tensile strength modulus of rapture and modulus of elostisity comparable to that of the FAO Standard. In general, the pH 5 produce medium density fiberboard of better physical properties.